Determinan Sosial Kesehatan Terhadap Kepatuhan Pengobatan Dots Penderita Tb Paru - Kartikasari Masting; Muhammad Syafar; Andi Yusuf (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; pulmonary TB is an infectious disease caused by Mycobacterium tuberculosis. Transmission occurs when a smear-positive pulmonary TB patient coughs or sneezes and the patient accidentally spreads germs into the air in the form of phlegm splashes. The purpose of this study was to determine the existence of social determinants of health on the compliance of dots treatment with pulmonary tuberculosis patients. Method; This research uses a descriptive-analytic method by using the